PENGARUH OBJEKTIVITAS, INTEGRITAS, PROFIL KAP, DAN KUALITAS AUDIT TERHADAP INDEPENSI AUDITOR - Fajarani, Septanti; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTPublic accountant or an independent auditor in auditing the client company has a strategic position as the thirdpartieswho carry out the duties and the responsibilities from the manager to audit the company financialstatement. Public accountant is the profession whichis trusted by the community. Public accountant is expectedas the neutral party who does not take side. The great trust from the usersof audited financial statements andother services which have provided by public accountants has requiredthe public accountant to notice theindependence in carrying out their tasks. This researchis meant to find out the influence of objectivity, integrity,KAP profile, and audit quality to the auditor independence. The data has been obtained by issuingquestionnaires to 50 respondents whoare the auditors in public accountant firm in Surabaya. The analysss hasbeen performed by using multiple linear regressions analysis. Based on the survey result, it has been revealedthat objectivity give significant influenceto the independence of the auditor, integrity give significant influencetothe independence of the auditor, KAP profile give significant influence to the independence of the auditor, andaudit quality give significant influence to the independence of the auditor in public accountant firm in Surabaya.Keywords: objectivity, integrity, KAP profile, audit quality, auditor independence